Gender Inequality and Its Representation in two African Novels. Things Fall Apart and The Joys of Motherhood. - Ayong , Quinta Njabi (My University, 2010)
Gender inequality is a social phenomenon that has been reverberating through society for decades and its prevalence could be seen both in the world of fiction and today's society. Women in most African societies have been at the centre of gender discourse as a result of marginalization and oppression by their male counterparts. Women have been excluded from public life, suppressed and relegated to the domestic sphere simply because of their femininity. Consequently, gender inequality remains persistent due to some social constraints, given the preference for men over women, as seen in most patriarchal high context societies, where gender equality has always been a far fetched dream as favouritism manifests itself in many different ways. In this study, Chinua Achebe's Things Fall Apart and Buchi Emecheta's The Joys of Motherhood, two subject oriented novels with divergent perspectives on gender issues and set in two different periods are studied. This comparative study seeks to analyse the role of women as represented in these novels. African women suffer from subordination due to gender role differences in the society. This gender discrimination is further perpetrated by a number of cultural factors that tend to limit women's opportunities in social life. The situation is exacerbated in their family and marriage life which is aimed at upholding the patriarchal values of Ibo culture. For women to be able to break through these obstacles and participate in public life, gender equality becomes an essential tool for their empowerment. A gender-free society improves the well being of families and communities. Thus, the use of fictional texts in analysing gender inequality as a social tool entertains, educates and helps change attitudes.
Keywords: Gender; Discrimination; Fiction; Ibo Novel; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|